Apcdd1 stimulates oligodendrocyte differentiation after white matter injury. Issue 10 (6th May 2015) - Lee, Hyun Kyoung; Laug, Dylan; Zhu, Wenyi; Patel, Jay M; Ung, Kevin; Arenkiel, Benjamin R.; Fancy, Stephen P. J.; Mohila, Carrie; Deneen, Benjamin
<x xml:space="preserve">Abstract</x> Wnt signaling plays an essential role in developmental and regenerative myelination of the CNS, therefore it is critical to understand how the factors associated with the various regulatory layers of this complex pathway contribute to these processes. Recently, Apcdd1 was identified as a negative regulator of proximal Wnt signaling, however its role in oligodendrocyte (OL) differentiation and reymelination in the CNS remain undefined. Analysis of Apcdd1 expression revealed dynamic expression during OL development, where its expression is upregulated during differentiation. Functional studies using ex vivo and in vitro OL systems revealed that Apcdd1 promotes OL differentiation, suppresses Wnt signaling, and associates with β‐catenin. Application of these findings to white matter injury (WMI) models revealed that Apcdd1 similarly promotes OL differentiation after gliotoxic injury in vivo and acute hypoxia ex vivo. Examination of Apcdd1 expression in white matter lesions from neonatal WMI and adult multiple sclerosis revealed its expression in subsets of oligodendrocyte (OL) precursors. These studies describe, for the first time, the role of Apcdd1 in OLs after WMI and reveal that negative regulators of the proximal Wnt pathway can influence regenerative myelination, suggesting a new therapeutic strategy for modulating Wnt signaling and stimulating repair after WMI. GLIA 2015;63:1840–1849